The mitochondrial protein Sod2 is important for the migration, maintenance, and fitness of germ cells - Tarbashevich, Katsiaryna; Ermlich, Laura; Wegner, Julian; Pfeiffer, Jana; Raz, Erez (Frontiers in Cell and Developmental Biology, 2023)
To maintain a range of cellular functions and to ensure cell survival, cells must control their levels of reactive oxygen species (ROS). The main source of these molecules is the mitochondrial respiration machinery, and the first line of defense against these toxic substances is the mitochondrial enzyme superoxide dismutase 2 (Sod2). Thus, investigating early expression patterns and functions of this protein is critical for understanding how an organism develops ways to protect itself against ROS and enhance tissue fitness. Here, we report on expression pattern and function of zebrafish Sod2, focusing on the role of the protein in migration and maintenance of primordial germ cells during early embryonic development. We provide evidence that Sod2 is involved in purifying selection of vertebrate germ cells, which can contribute to the fitness of the organism in the following generations.